Musculoskeletal Treatment Mechanisms: A Puzzle That May Never Be Fully Solved - Chad E. Cook; Damian L. Keter (Journal of Orthopaedic & Sports Physical Therapy, 2026)
SYNOPSIS: Musculoskeletal treatments often appear simple, yet the mechanisms underlying their effects remain difficult to explain. Patients and clinicians routinely ask why exercises, manual techniques, or psychologically informed interventions help, but current evidence rarely supports the intuitive explanations offered in practice. Although mechanistic research promises more precise and individualized care, most studies isolate single pathways under controlled conditions that fail to reflect the complexity of human recovery. In real-world musculoskeletal care, physiological, psychological, and social processes interact continuously, producing therapeutic effects that are multifactorial, dynamic, and only partially measurable. This interconnectedness creates an inverse relationship between what is easy to study and what meaningfully explains clinical outcomes. Persistent uncertainty should not be interpreted as treatment inefficacy but as a reflection of living systems in which no single mechanism dictates recovery. Embracing complexity allows the field to move beyond reductionist debates and toward more meaningful scientific and clinical questions. J Orthop Sports Phys Ther 2026;56(9):569-570. Epub 3 Jun 2026. doi:10.2519/jospt.2026.14486